2019
DOI: 10.1097/der.0000000000000498
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Identification and Confirmation of Contact Allergens

Abstract: Identification of the etiological chemical agent(s) associated with a case(s) of allergic contact dermatitis (ACD) is important for both patient management and public health surveillance. Traditional patch testing can identify chemical allergens to which the patient is allergic. Confirmation of allergen presence in the causative ACD-associated material is presently dependent on labeling information, which may not list the allergenic chemical on the product label or safety data sheet. Dermatologists have expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…23 Several studies have shown that NAT1 activity is detectable in the cytosol in different tissues in humans and animals. 9,16,24,25 In this study, we reconfirmed that NAT1 can indeed be considered as a cytosolic enzyme, as we showed NAT1 to be expressed in human skin cytosol.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…23 Several studies have shown that NAT1 activity is detectable in the cytosol in different tissues in humans and animals. 9,16,24,25 In this study, we reconfirmed that NAT1 can indeed be considered as a cytosolic enzyme, as we showed NAT1 to be expressed in human skin cytosol.…”
Section: Discussionsupporting
confidence: 66%
“…The ROAT is performed without occlusion; therefore, the potential development of irritant and false-positive reactions is minimized. 24,25 If dermatitis occurs at the ROAT test site, a contact allergy to the product is strongly suspected. Notably, a product may contain skin irritants that create an inflammatory environment, in which case the threshold for an elicitation reaction is lowered.…”
Section: Irritant Reaction Irmentioning
confidence: 99%
See 3 more Smart Citations